2016
DOI: 10.1038/srep20970
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment and ramifications of a purported marine trophic cascade

Abstract: When identifying potential trophic cascades, it is important to clearly establish the trophic linkages between predators and prey with respect to temporal abundance, demographics, distribution, and diet. In the northwest Atlantic Ocean, the depletion of large coastal sharks was thought to trigger a trophic cascade whereby predation release resulted in increased cownose ray abundance, which then caused increased predation on and subsequent collapse of commercial bivalve stocks. These claims were used to justify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 48 publications
0
61
0
1
Order By: Relevance
“…Sufficient information of reef ecology such as spatiotemporal abundance, distribution, habitat associations, environmental inputs, diet, and life history of a species is necessary to inform ecological roles and function (Figure 2). While recent examples of poor management decisions have created a need for standardizing approaches in the field of trophodynamics (Grubbs et al, 2016), studies are still omitting key concepts before implementing applied research. We have highlighted such studies in relation to popular methods, but also identified recent research that is incorporating and combining new methods to account for some of the challenges faced within the field.…”
Section: Challenges and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sufficient information of reef ecology such as spatiotemporal abundance, distribution, habitat associations, environmental inputs, diet, and life history of a species is necessary to inform ecological roles and function (Figure 2). While recent examples of poor management decisions have created a need for standardizing approaches in the field of trophodynamics (Grubbs et al, 2016), studies are still omitting key concepts before implementing applied research. We have highlighted such studies in relation to popular methods, but also identified recent research that is incorporating and combining new methods to account for some of the challenges faced within the field.…”
Section: Challenges and Discussionmentioning
confidence: 99%
“…Even if assumed cascading events are observed such as phase shifts, finding the cause of such patterns at large spatial scales is challenging (Dulvy et al, 2004). Attention should also be paid to temporal gradients over which cascades occur, considering life-history and growth capabilities of populations as well as lagged effects from perturbations that can occur over extended time periods (Dulvy et al, 2004;Grubbs et al, 2016). The difficulty in linking trophic levels to the same event that categorizes a trophic cascade is difficult to support empirically, particularly when most reefs are already in a degraded state from external stressors.…”
Section: Controlling Forces In Trophodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing list of studies that question the viability of the trophic-cascade hypothesis in the marine environment (e.g., Grubbs et al 2016;Sinclair et al 2015) and those that refute the arguments of Frank et al, providing evidence against top-down forcing by cod on adult snow crab (Chabot et al 2008;Émond et al 2015), showing the lack of evidence for pelagic fish affecting the recovery of cod (Swain and Mohn 2012), presenting evidence for bottom-up control of phytoplankton by herbivorous zooplankton (Head and Pepin 2010;Head and Sameoto 2007), and even contesting the methodology used to detect the ESS trophic cascade (Pershing et al 2015). We are unaware of any studies providing independent support of the PO hypothesis, although many studies have relied on its conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the causes of the collapse, the lack of recovery of east coast cod populations to their former numbers despite over 25 years of low fishing effort and moratoria has been well documented (Bundy and Fanning 2005;Smedbol and Wroblewski 2002;Swain and Mohn 2012) and its causes and consequences extensively debated in terms of regime shifts, top-down versus bottom-up trophic dynamics, and more recently "oscillatory runaway consumption dynamics of the forage fish complex" (Frank et al 2005(Frank et al , 2011Greene 2013;Greene et al 2012;Greene and Pershing 2007;Grubbs et al 2016;Pershing et al 2015;Sinclair et al 2015).…”
Section: Introductionmentioning
confidence: 99%